The Influence of Supervisors’ Communication Style, Empathy, and Support on Employee Loyalty, Mediated by Emotional Intelligence Management: A PLS-SEM Analysis - Alvhiny Alvhiny; Ilona Vicenovie Oisina Situmeang (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Employee loyalty is a crucial factor in supporting organizational sustainability and effectiveness. However, various studies have shown that loyalty is influenced not only by structural factors but also by the quality of relationships between supervisors and subordinates. This study aimed to analyze the influence of supervisors’ communication style, empathy, and support on employee loyalty through emotional intelligence management as a mediating variable. The study was grounded in Social Exchange Theory and Organizational Support Theory, which explain that the quality of social interactions in the workplace can shape employees’ positive attitudes and behaviors toward the organization. This study used a quantitative approach with a survey method involving 205 employees. The sampling technique was purposive sampling, while the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that supervisors’ communication style had a positive and significant effect on employees’ emotional intelligence management (? = 0.195; p < 0.05). Conversely, supervisors’ empathy and support did not significantly influence emotional intelligence management. In addition, emotional intelligence management did not significantly influence employee loyalty and was unable to mediate the relationship between supervisors’ communication style, empathy, or support and employee loyalty. These findings indicate that supervisors’ communication plays an important role in shaping employees’ emotional management abilities, but employee loyalty is a more complex construct influenced by other factors outside the research model. This study contributes to the development of organizational communication studies by demonstrating that the effectiveness of supervisors’ communication is more relevant to developing employees’ psychological aspects than to directly forming loyalty. These findings also provide opportunities for further research to explore other factors that contribute to increasing employee loyalty.